Coal-based sulfur hybrid sorbent for removal of Hg0 from flue gas. Part 2. High organic sulfur coal. (1st July 2023) - Huo, Qihuang; Wang, Yahui; Chen, Huijun; Feng, Yu; Han, Lina; Bao, Weiren; Chang, Liping; Wang, Jiancheng; Xie, Kechang
Graphical abstract: Highlights: A two-step craft was proposed to prepare Hg 0 sorbent from high organic sulfur coal. Fe2 O3 doping changed organic sulfur to FeSx during carbonization process. KOH changed FeSx to various active sulfur during activation process. This two-step craft can be expanded to other organic sulfur materials. Abstract: It is a win–win strategy to prepare mercury sorbents from low-cost high-sulfur raw materials. In part 1, mercury sorbents with excellent performance were prepared from high inorganic sulfur coal through KOH activation. However, this method does not work for high organic sulfur coal. In this work, a two-step preparation method is developed to prepare mercury sorbents from high organic sulfur coal. The first step is the co-pyrolysis/carbonization of Fe2 O3 and coal, during which organic sulfur in coal is converted into FeSx . XPS shows that the percentage of Sx 2– /S on the surface of the carbonized samples gradually increases from 5.4% to 22.2% with the m(Fe):m(So ) ratio from 0:4 to 5:4. The second step is KOH activation, and it converts FeSx into various S species, including C-S, S 0, S2 2− and S 2− . Among the prepared mercury sorbents, LF+3Fe/4S-A (m(Fe):m(So ) = 3:4) shows the best mercury removal performance, and its mercury removal efficiency remains above 84% for 120 min under N2 +O2 at 120 °C. The Hg-TPDD and XPS results indicate that S*, including C-S, S 0 and S2 2−, are the major active sites for mercury removal rather than Fe element, and HgS is the main existing form of mercury on the used sorbents. Besides LF coal, this two-step process is also applicable to other high organic sulfur coals (such as LL coal, WJZ coal, and SY coal) and high-sulfur petroleum coke.